Molecular taxonomy of myelodysplastic syndromes and its clinical implications - Bernard, Elsa; Hasserjian, Robert P; Greenberg, Peter L; Arango Ossa, Juan E; Creignou, Maria; Tuechler, Heinz; Gutierrez-Abril, Jesus; Domenico, Dylan; Medina-Martinez, Juan S; Levine, Max; Liosis, Konstantinos; Farnoud, Noushin; et al. (Blood, 2024)
Myelodysplastic syndromes (MDS) are clonal hematologic disorders characterized by morphologic abnormalities of myeloid cells and peripheral cytopenias. Although genetic abnormalities underlie the pathogenesis of these disorders and their heterogeneity, current classifications of MDS rely predominantly on morphology. We performed genomic profiling of 3233 patients with MDS or related disorders to delineate molecular subtypes and define their clinical implications. Gene mutations, copy-number alterations, and copy-neutral loss of heterozygosity were derived from targeted sequencing of a 152-gene panel, with abnormalities identified in 91%, 43%, and 11% of patients, respectively. We characterized 16 molecular groups, encompassing 86% of patients, using information from 21 genes, 6 cytogenetic events, and loss of heterozygosity at the TP53 and TET2 loci. Two residual groups defined by negative findings (molecularly not otherwise specified, absence of recurrent drivers) comprised 14% of patients. The groups varied in size from 0.5% to 14% of patients and were associated with distinct clinical phenotypes and outcomes. The median bone marrow (BM) blast percentage across groups ranged from 1.5% to 10%, and the median overall survival ranged from 0.9 to 8.2 years. We validated 5 well-characterized entities, added further evidence to support 3 previously reported subsets, and described 8 novel groups. The prognostic influence of BM blasts depended on the genetic subtypes. Within genetic subgroups, therapy-related MDS and myelodysplastic/myeloproliferative neoplasms had comparable clinical and outcome profiles to primary MDS. In conclusion, genetically-derived subgroups of MDS are clinically relevant and might inform future classification schemas and translational therapeutic research.
Keywords: mutace; DNA Copy Number Variations; dospělí; Female; Adult; ženské pohlaví; variabilita počtu kopií segmentů DNA; lidé; Mutation; Aged, 80 and over; Loss of Heterozygosity; prognóza; Myelodysplastic Syndromes; myelodysplastické syndromy; Male; ztráta heterozygozity; Aged; Prognosis; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans